Penguatan Pendidikan Karakter Peduli Lingkungan pada Peserta Didik di SMA Negeri 1 Sukorejo Kabupaten Kendal - Lusiana Fitrianingsih; Masrukhi (Universitas Negeri Semarang, 2025)
The lack of awareness among some people regarding environmental sustainability causes environmental damage. Efforts made to build public awareness of environmental sustainability can be done through an educational process. Schools as formal educational institutions have an important role in providing awareness to students to care about the environment. The aims of this research are (1) to examine the implementation of environmentally caring character education at SMA Negeri 1 Sukorejo; (2) analyze efforts to strengthen environmental care character education at SMA Negeri 1 Sukorejo. This research uses a qualitative case study method. The data collection techniques used were interviews, observation and documentation. Test the validity of the data using the Triangulation model. Data analysis uses data collection, data reduction, data presentation and drawing conclusions. The research results show that (1) the implementation of environmental care character education at SMA Negeri 1 Sukorejo was carried out through the Adiwiyata program by applying the concepts of exemplary and integration. The implementation of environmental care character education at SMA Negeri 1 Sukorejo is included in school management. The implementation strategy is carried out through routine activities, spontaneous activities, example and conditioning; (2) Efforts to strengthen character education that cares about the environment at SMA Negeri 1 Sukorejo are carried out through school activities (intracurricular, co-curricular and extra-curricular) and school culture.